The Internalization Of Islamic Values In The Learning Of Aqidah Akhlak In Shaping The Character Of Students At Man 1 Bone - A. Mustika Abidin (IAIN Ambon, 2022)
Abstract: This study aims to describe the internalization of Islamic values in the learning of moral aqidah in shaping the character of students at MAN 1 Bone. This research uses empiricism qualitative research. The results showed that: 1) The form of internalization of Islamic values in the learning of moral aqidah in shaping the character of students which was applied by the teacher was by internalizing the value of monotheism, the value of aqidah/faith, moral values, sharia values, and the value of Insan Kamil, 2) Method internalization of Islamic values in the learning of moral aqidah applied by teachers, namely using the lecture method, question and answer, group discussions, stories/examples, creating a conducive atmosphere, habituation, instilling and enforcing discipline, giving good advice, using media/technology, and doing field trips or nature tadabur in shaping the character of students at MAN 1 Bone, 3) The implication of internalizing Islamic values on learning aqidah and morals in shaping the character of students at MAN 1 Bone causes students to always be active, obedient, and subject to the rules, both individually as well as intellectually-religiously. Another implication is that it has a positive impact on the minds, attitudes, and souls of students so that various changes appear that result in the formation of good character. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan internalisasi nilai-nilai Islam pada pembelajaran akidah akhlak dalam membentuk karakter siswa di MAN 1 Bone. Penelitian ini menggunakan penelitian kualitatif empirisme. Hasil penelitian menunjukkan bahwa: 1) Bentuk internalisasi nilai-nilai Islam pada pembelajaran akidah akhlak dalam membentuk karakter siswa yang diterapkan oleh guru yaitu dengan menginternalisasikan nilai tauhid, nilai akidah/keimanan, nilai akhlak, nilai syariah, dan nilai Insan kamil, 2) Metode internalisasi nilai-nilai Islam pada pembelajaran akidah akhlak yang diterapkan oleh guru yaitu menggunakan metode ceramah, tanya jawab, diskusi kelompok, kisah/keteladanan, menciptakan suasana yang kondusif, pembiasaan, penanaman dan penegakan kedisiplinan, memberikan nasihat yang baik, menggunakan media/teknologi, dan melakukan karyawisata atau tadabur alam dalam membentuk karakter siswa di MAN 1 Bone, 3) Implikasi internalisasi nilai-nilai Islam pada pembelajaran akidah akhlak dalam membentuk karakter siswa di MAN 1 Bone menyebabkan siswa selalu aktif, patuh, dan tunduk terhadap aturan-aturan, baik secara individu-kelompok maupun secara intelektual-agama. Implikasi lainnya yaitu, memberi dampak positif bagi pikiran, sikap, dan jiwa siswa sehingga muncul berbagai perubahan yang mengakibatkan terbentuknya karakter yang baik.